Transformasi Branding UMKM Snack Mak Asih: Penguatan Branding dan Pemasaran Berkelanjutan di Desa Jawa Tengah - Nur Safitri Yeni; Helma Malini; Auryn Sela Vashti; Cristalia Sandra Irena; Muhammad Raihan Afrizy (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2025)
UMKM are crucial to local economies but constantly struggle with branding and digital marketing. This community service program supported Snack Mak Asih, an UMKM in Dusun Karya 1, Desa Jawa Tengah, Sungai Ambawang District, by strengthening its brand identity and marketing strategies. Using Participatory Learning and Action (PLA) and Service-Learning approaches, the program empowered university students as facilitators. The activities included designing effective product labels, creating eye - catching packaging, and using social media for digital promotion. The results clearly showed the UMKM participants grasping the importance of branding. The proactively making their own product label's and now they are ready to facing the modern market demands. This program not only enhanced product value but also highlighted the innovation in a competitive market. This intervention has proven its positive impact on business sustainability and bosted UMKM contribution to rural economic development.